1985
DOI: 10.1121/1.392779
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and enhancement of spectral structure by the cochlea

Abstract: The intensity dependence of signal processing in the cat cochlea was studied in responses of single auditory-nerve fibers for harmonic complexes having various amplitude and phase spectra. Analyses were based on information present in temporal discharge cadences, and they consisted of assessing Fourier spectra of period histograms synchronized to the period of the waveform fundamental. At low intensities, response spectra resembled filtered versions of the stimulus spectrum, with the amounts of filtering being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Two other studies using flat-spectrum multitone stimuli reported that the response spectra obtained at low intensities of presentation resembled threshold tuning curves (Horst et al, 1985(Horst et al, , 1986. From their figures, the response spectra indeed broadened at high intensities (e.g., see Fig.…”
Section: B Comparisons With Previous Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Two other studies using flat-spectrum multitone stimuli reported that the response spectra obtained at low intensities of presentation resembled threshold tuning curves (Horst et al, 1985(Horst et al, , 1986. From their figures, the response spectra indeed broadened at high intensities (e.g., see Fig.…”
Section: B Comparisons With Previous Studiesmentioning
confidence: 83%
“…The only study prior to ours that used multitones with one component's amplitude incremented has appeared only recently (Horst et al, 1985). This study was very brief, citing results from only one fiber, with only one probe component (at the fiber's CF), and with only three levels of the amplitude increment.…”
Section: B Comparisons With Previous Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…This "multiple phase locking" can be found in several studies in which the response to harmonic tone complexes was analyzed (Young and Sachs, 1979;Evans, 1981;Horst et al, 1985). One may view such data as a "collection of separate R values," but the identification of the R values with Fourier components suggests a more natural, spectral interpretation of multiple phase locking.…”
Section: Methodsmentioning
confidence: 97%
“…The current study limited the measurement to increment detection thresholds largely due to this fact as well as that the usage of a harmonic spectrum did not lend itself to a frequency discrimination task. Despite the fact that at high levels an increment may have a fairly broad excitation, literature has consistently shown that the important aspect of neural coding an increment ͑or formant͒ in a broadband spectrum ͑e.g., a vowel spectrum͒ is through synchrony and not neural excitation, and even at high presentation levels that cause a broadband excitation, the frequency specificity of synchrony was maintained ͑Sachs and Young, 1980;Horst et al, 1985͒. In this manner, if a spectral peak can be "reintroduced" into the signal, it follows that regardless of the bandwidth of excitation, synchrony will increase local to the place of the spectral peak in a similar way that formants are coded at higher levels. Therefore, an algorithm that can partially restore the spectral representation of speech will likely improve speech intelligibility.…”
Section: Discussionmentioning
confidence: 88%